Responsabilidade social universitária e a formação cidadã - Ribeiro, Raimunda Maria da Cunha (2013)
The social responsibility of the university is a phenomenon that has gain eminence in the debate of the superior education; is a social concept and politically built; it concerns to the development promoted by the university in this followed dimensions: social, cultural, environmental and economic. Such dimension represents the challenge that the university needs to fill the bill, in the perspective of its modernization. However, the debate about university social responsibility is complex and presents some tensions, that by one‟s turn are reflexion of social field. This study about politic of university social responsibility was elaborated in the line of formation, politics and practices in education of the postgraduation program in education of PUCRS and suggested: to understand how was been built the concept of university social responsibility , in regard to the knowledge and promotion of the development in its multiple dimensions; how the university establishes in its statue the actions of social responsibility; how are been done the challenges and/or compromise of the university in terms of teaching research, extention and management, to attend social and educational claim. The methodological abordage adopted in this study was qualitative, that delineated itself in two perspectives: study of the public universities and 27 Brazilian Federal- Public universities; and a study in the university Estadual do Piauí/Brazil. To the realization of this research were adopted two techinics of data collect: document analysis ( oriented by documental analysis principles) and semi structure interviews. The analysed documents were the statue of the 43 universities participants of this investigation; the semi structure was made with 10 (ten) participants, members of the Conselho Universitário da Universidade Estadual do Piauí. The data were analysed based on the technic of analysis of contents, meanly from Bardin theory. To better understand the concept of social responsibility, its origin, tendency and tension, it‟s necessary revisit other fields as the administration, politic science and the economy. The university social responsibility isn‟t a definitive proposal, neither a dogmatic strategy that must be adopted by the institutions, but configures as a modernization alternative, that permit s the constant search of the redefinition of the responsibly permanent social and critic about the way of the thinking and adopt the educational process. The social responsibility of the universities forms a link between the knowledge generated in the context of its application and the local necessities, national and global. it can be like, the link between the knowledge institutionally generated and the impacts in the society in therms of development